Morpho-phonological levels and grammaticalization in Karimojong: A review of the evidence - Diane Lesley- Lesley-Neuman (LibraryPress@UF, 2012)
An analysis of the affixation processes and the phonological rules governing [ATR] harmony in Karimojong verbs permits the organization of derivational processes into three levels. On each level specific groups of morphemes are affixed and the resultant derived words undergo defined sets of phonological processes. On Level 1 a feature filling [±ATR] harmony rule applies, in which the [ATR] feature spreads bi-directionally from the principal root vowel across the root and all Level 1 affixes. However, there are also localized disharmonic domains created by phonologized co-articulation effects of consonants and dissimilation rules for vowels. On Level 2, suffixation of Tense-Mood-Aspect (TMA) markers at the right edge of the verbal complex triggers [+ATR] feature spreading leftward across the derived word. On Level 3 affixation does not trigger [ATR] harmony processes, and both affix vowels and the derivational complexes to which they are added retain their [ATR] features. Some Karimojong affixes exhibit behaviors characteristic of two different levels, depending on context; these affixes are proposed to be in transition between levels. The three levels are proposed to result from diachronic evolution, and their relative chronological development can be established by (1) correspondences to landmarks within the cross-linguistically attested agreement system grammaticalization cline, which groups affixes according to ordering universals, and (2) the existence of successive evolutionary cycles of frequentive morphology. A model of the morphology-phonology interface is proposed in which linguistic structure internal to the morpheme channels the spread of [ATR] features. The model provides an explanation for surface irregularities that originated at the time of areal vowel mergers in Nilotic languages (Dimmendaal, 2002).